Conversations with Thaksin from exile to deliverance : Thailand's populist tycoon tells his story - Plate, Tom. (New York Marshall Cavendish Corp, 2011)
Going home is an iconic theme of literature and music that touches everyone?s heart. Bur rarely has that journey looked more like an impossible dream than for Thaksin Shinawatra, the much loved and much hated former prime minister of Thailand. Expelled from the former Siam by a military coup in 2006, the cell-phone billionaire retreated to a dacha in Dubai to bide his time and plot his triumphant return.
Includes bibliographical references
Keywords: Thaksin Chinnawat, 1949- -- Interviews; Prime ministers -- Thailand -- Interviews